2018
DOI: 10.1186/s12888-018-1870-0
|View full text |Cite
|
Sign up to set email alerts
|

Personality functioning in anxiety disorders

Abstract: BackgroundThe Alternative DSM-5 Model for Personality Disorders as well as the upcoming IDC-11 have established a new focus on diagnosing personality disorders (PD): personality functioning. An impairment of self and interpersonal functioning in these models represents a general diagnostic criterion for a personality disorder. Little is known so far about the impairment of personality functioning in patients with other mental disorders than PD. This study aims to assess personality functioning in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
(24 reference statements)
2
28
3
1
Order By: Relevance
“…Additional aims might focus on the predictive power of the levels of personality functioning on various outcomes, test-retest reliabilities, effects of treatments, and discrepancies of answers with other sources of information. Moreover, it was suggested that personality functioning is related not only to personality disorders but also to other mental disorders, for example, anxiety (Doering et al, 2018). Therefore, future studies might focus on the personality functioning in other mental disorders or personality dimensions.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional aims might focus on the predictive power of the levels of personality functioning on various outcomes, test-retest reliabilities, effects of treatments, and discrepancies of answers with other sources of information. Moreover, it was suggested that personality functioning is related not only to personality disorders but also to other mental disorders, for example, anxiety (Doering et al, 2018). Therefore, future studies might focus on the personality functioning in other mental disorders or personality dimensions.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Conceptually, this approach distinguishes PDs from other mental disorders by identifying the shared commonalities of people with PD (Bach & Hutsebaut, 2018). Moreover, clinicians and researchers gain a better understanding of the diagnosis and possible treatment of mental disorders by assessing the impairment of personality functioning (Doering et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need of further studies examining if the current personality differences are specific for SAD and if they are generalizable across epidemiological-clinical samples and culturally diverse populations. Also, the current SAD clusters should ideally be compared, not only on social anxiety symptom severity, but also on personality functioning, involving self (identity, direction) and interpersonal (empathy, intimacy) dimensions demonstrated to be impaired in anxiety disorders [88]. Assessment of personality functioning has been added to the alternative diagnostic model for personality disorders in DSM-5.…”
Section: Limitationsmentioning
confidence: 99%
“…Diese Befunde sprechen sowohl für einen dimensionalen Ansatz als auch für die Bedeutung des PN als übergeordneten Faktor 9 in der Konzeptualisierung und Diagnostik von Angstzuständen. Der klinische Nutzen der Erfassung des PN bei Patienten mit Angststörungen deckt sich zudem mit theoretischen Annahmen psychodynamischer Theorien 10 .…”
Section: Dimensionale Betrachtung Von Angstproblematiken Im Kontext B...unclassified